Soldiers of Song : The Dumbells and Other Canadian Concert Parties of the First World War - Wilson, Jason, 1970- (Book collections on Project MUSE., 2012)
"The irreverent humour that inspired the likes of The Wayne and Shuster Hour and Monty Python was born in the trenches of the First World War, and The Dumbells -- fighting soldiers who entertained at concert parties -- were central to that birth. Soldiers of Song tells their story. Lucky soldiers who could sing a song, perform a skit, or pass as a "lady," were taken from the line and put onstage for the benefit of their soldier-audiences. The intent was to bolster morale and thereby help soldiers survive the war. The Dumbells' popularity was not limited to troop shows along the trenches. The group managed a run in London's West End and became the first Canadian production to score a hit on Broadway. Touring Canada for some twelve years after the war, the Dumbells became a household name and made more than twenty-five audio recordings. If nationhood was won on the crest of Vimy Ridge, it was the Dumbells who provided the country with its earliest soundtrack. Pioneers of sketch comedy, the Dumbells are as important to the history of Canadian theatre as they are to the cultural history of early-twentieth-century Canada."--Back cover